Carotid geometry is independently associated with complicated carotid artery plaques - Strecker, Christoph; Kopczak, Anna; Saam, Tobias; Sepp, Dominik; Hennemuth, Anja; Mayerhofer, Ernst; Poli, Sven; Ziemann, Ulf; Poppert, Holger; Schindler, Andreas; Harloff, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Introduction Complicated carotid artery plaques (cCAPs) are associated with an increased risk of rupture and subsequent stroke. The geometry of the carotid bifurcation determines the distribution of local hemodynamics and could thus contribute to the development and composition of these plaques. Therefore, we studied the role of carotid bifurcation geometry in the presence of cCAPs. Methods We investigated the association of individual vessel geometry with carotid artery plaque types in the Carotid Plaque Imaging in Acute Stroke (CAPIAS) study. After excluding arteries without plaque or with insufficient MRI quality, 354 carotid arteries from 182 patients were analyzed. Individual parameters of carotid geometry [i.e., internal carotid artery (ICA)/common carotid artery (CCA) ratio, bifurcation angle, and tortuosity) were derived from time-of-flight MR images. The lesion types of carotid artery plaques were determined according to the American Heart Association classification of lesions by multi-contrast 3T-MRI. The association between carotid geometry and a cCAP was studied using logistic regression after adjusting for age, sex, wall area, and cardiovascular risk factors. Results Low ICA/CCA ratios (OR per SD increase 0.60 [95%CI: 0.42–0.85]; p = 0.004) and low bifurcation angles (OR 0.61 [95%CI: 0.42–0.90]; p = 0.012) were significantly associated with the presence of cCAPs after adjusting for age, sex, cardiovascular risk factors, and wall area. Tortuosity had no significant association with cCAPs. Only ICA/CCA ratio remained significant in a model containing all three geometric parameters (OR per SD increase 0.65 [95%CI: 0.45–0.94]; p = 0.023). Conclusions A steep tapering of the ICA relative to the CCA and, to a lesser extent, a low angle of the carotid bifurcation were associated with the presence of cCAPs. Our findings highlight the contribution of bifurcation geometry to plaque vulnerability. Thus, assessment of carotid geometry could be helpful in identifying patients at risk of cCAPs.